Effect of a Specific Questionnaire Sheet on Subclassification of Osteonecrosis of the Femoral Head - Hatanaka, Hiroyuki (Med Sci Monit, 2020)
BACKGROUND: This study examined whether use of a specific questionnaire sheet for nontraumatic osteonecrosis of the femoral head (ONFH) could affect the subclassification of ONFH compared with a conventional medical interview. MATERIAL/METHODS: Study participants consisted of 400 patients with ONFH who visited our hospital between February 2011 and March 2015. Data on history of systemic steroid therapy and habitual alcohol intake were obtained during a conventional medical interview at the first visit and were re-evaluated using a specific questionnaire sheet at another visit. Patients were subclassified into 4 groups: steroid-associated, alcohol-associated, steroid/alcohol-associated, or idiopathic ONFH. RESULTS: Use of the specific questionnaire sheet resulted in a 4.0% increase in the proportion of patients with a history of systemic steroid therapy, from 57.3% (n=229) to 61.3% (n=245), and a 14.3% increase for history of habitual alcohol intake, from 35.0% (n=140) to 49.3% (n=197). The proportion of patients with steroid/alcohol-associated ONFH increased from 2.5% (n=10) to 17.8% (n=71), while the proportion in the other 3 groups decreased: steroid-associated ONFH from 54.8% (n=219) to 43.5% (n=174); alcohol-associated ONFH from 32.5% (n=130) to 31.5% (n=126); and idiopathic ONFH from 10.2% (n=41) to 7.2% (n=29). Ninety-six patients (24.0%) were classified into a different subgroup based on the specific questionnaire sheet. CONCLUSIONS: The use of a specific questionnaire sheet can change the distribution of ONFH subclassifications compared with use of a conventional medical history interview. Use of a specific questionnaire sheet can allow for more detailed self-reporting regarding potential causative factors for nontraumatic ONFH, especially habitual alcohol intake.